0086 Shiftwork, circadian disruption and breast cancer: a first application of the chronobiological theory and practical challenges within the australian bcee study. (21st August 2017) - Fritschi, Lin; Groß, Valèrie; Wild, Ursula; Heyworth, Jane; Glass, Deborah; Erren, Thomas
Abstract : Background: In 2007, the International Agency for Research on Cancer [IARC] classified shiftwork involving circadian disruption [CD] as probably carcinogenic to humans. We hypothesised that CD occurs if individuals work during their preferred sleep time (i.e. their biological nights). Objective: We intended to refine the measure of exposure to shiftwork involving CD within the Breast Cancer, Environment and Employment Study (BCEES). Methods: For each participant, we classified jobs with regard to whether their work times overlapped with their individual biological night. Preferred sleep times were obtained through the first two questions of the Horne-Östberg morningness-eveningness questionnaire [MEQ] ("perfect day" approach Groß et al., Medical Hypotheses 2017). Results: Re-classifications were confined to shifts which include work - in part or in full - between midnight and 7 am. Circadian disruption was defined as an overlap of the preferred sleep time and the assessed shift times (+2 hours e.g. for travelling). We found a small, non-statistically significant association between shiftwork involving CD and breast cancer risk not different from prior results (Fritschi et al., British Journal of Cancer 2013). Assessment of total CD was limited as numbers of chronodisrupted shifts associated with work between 0000–0700 and working times such as 0800–1600 or 1400–2200 could not be assessed. Conclusions: Whether accumulated CD doses due to variable work times during variable individual biological nights are carcinogenic must remain open at this stage. To provide interpretable answers, information on all shifts during the working life with potential CD for individuals with different biological nights must be considered.